Mechanisms of photodynamic inactivation of herpes simplex viruses: comparison between methylene blue, light plus electricity, and hematoporhyrin plus light. - Schnipper, L E (1980)
Herpes simplex virus (HSV) types 1 and 2 have been inactivated in vitro using low concentrations of methylene blue (MB), light (lambda) plus electricity (E), or hematoporphyrin derivative (HPD) plus lambda. Both techniques introduce single strand interruptions into viral DNA, but do not make double strand ruptions into viral DNA, but do not make double strand breaks. MB, lambda plus E-treated virions adsorb normally to and penetrate susceptible cells, whereas HSV inactivated with HPC and light does not. This difference is emphasized by the induction of new viral and cell DNA synthesis after infection with MB, lambda plus E-treated virions, whereas only cell, DNA but no HSV DNA, is made subsequent to HPD and lambda exposure. These observations reflect disparate mechanisms of viral inactivation. A block(s) in viral maturation, subsequent to viral DNA synthesis, occurs as a result of treatment with MB, lambda and E, whereas HPD plus lambda-treated particles fail to enter a susceptible cell, and therefore do not initiate an infection.